1988
DOI: 10.3168/jds.s0022-0302(88)79700-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Udder Preparations on Intramammary Infections

Abstract: Udder preparations of wet towel plus drying and .1% iodophor premilking teat dipping plus drying were compared with no preparation to determine effects on number of new intramammary infections. Teats of 84 cows were challenged (5 d/wk) for 18 wk with a culture broth of Streptococcus uberis 3 h prior to each p.m. milking to stimulate environmental contamination. Wet towel plus drying and premilking teat dipping plus drying significantly reduced number of new intramammary infections compared to no preparation. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 7 publications
1
25
0
4
Order By: Relevance
“…A larger difference in infection rates and SCC between treatments, over the trial period, may have been observed if the initial cow SCC was higher at the trial start date. The prevalence of intramammary infection is highly correlated with the number of mastitis pathogens on the teat end at milking (Galton et al, 1988). Advantages in terms of reduced bacterial levels in milk have been highlighted when teats are dry prior to cluster application (McKinnon et al, 1983;Galton et al, 1986).…”
Section: Discussionmentioning
confidence: 88%
“…A larger difference in infection rates and SCC between treatments, over the trial period, may have been observed if the initial cow SCC was higher at the trial start date. The prevalence of intramammary infection is highly correlated with the number of mastitis pathogens on the teat end at milking (Galton et al, 1988). Advantages in terms of reduced bacterial levels in milk have been highlighted when teats are dry prior to cluster application (McKinnon et al, 1983;Galton et al, 1986).…”
Section: Discussionmentioning
confidence: 88%
“…The effect of disinfection agents on hygienic milk quality and total bacterial contamination on cows teats has been evaluated in many studies (Galton et al, 1986;Galton et al, 1988;Nickerson, 2001;Ruegg, 2003). Other researchers (Kumar et al, 2012) also show that the use of some disinfectant products prior milking can have beneficial effects on reducing the levels of total bacterial, staphylococcal and streptococcal pathogens on teat skin.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate hygiene conditions increase the risk of penetration of microorganisms present on the udder from the tip of teats into the teat canal which could result in mammary gland inflammation (Pavičic et al, 2003). Premilking udder hygiene includes many factors, such as dryness and cleanliness of teats and udder, type of drying towel used, type and concentration of premilking sanitiser or antiseptic, and sanitiser contact time with teats (Galton et al, 1986;1988;Nakano et al, 1995). Premilking teat preparation not only reduces environmental bacteria on the teat surface but also reduces bacteria counts in milk (Ruegg, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tem sido descrito que a antissepsia dos tetos e secagem com papel toalha antes da ordenha reduzem a contagem bacteriana da pele dos tetos e do leite (GALTON et al, 1982;MERRILL, 1986;INGAWA;GOUGH, 1992), além de prevenir infecções intramamárias (GALTON; MERRIL, 1988;SCHULTZE, 1985). (1988), objetivando determinar os efeitos do pré-dipping em comparação à não higienização dos tetos antes da ordenha sobre a incidência de novas infecções intramamárias, comprovou uma redução de 66,3% no número de novas infecções por Streptococcus uberis inoculada experimentalmente.…”
Section: Brito Brito E Vernequeunclassified